2019
DOI: 10.17138/tgft(7)437-444
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of cattle fattening systems based on forage tree legume diets in eastern Indonesia

Abstract: Keynote paper presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.Research and government agencies in eastern Indonesia have identified 2 systems with potential to increase productivity and incomes of small-holder cattle producers: improved cattle feeding practices through forage tree legumes (FTL); and the development of more efficient and specialized cattle-fattening systems. Extensive research has been conducted on production and technical aspects of FTL-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Waldron conducted an analysis of our key leucaena sites and reported that: "Under all measures of profitability, representative (cattle fattening) households at all sites were profitable in the wet season. As expected, 'return to person days' in the dry season were lower than average off-farm wages" due to reduced leucaena biomass productivity and hence the number of cattle raised per household [11].…”
Section: Economic Impactssupporting
confidence: 64%
“…Waldron conducted an analysis of our key leucaena sites and reported that: "Under all measures of profitability, representative (cattle fattening) households at all sites were profitable in the wet season. As expected, 'return to person days' in the dry season were lower than average off-farm wages" due to reduced leucaena biomass productivity and hence the number of cattle raised per household [11].…”
Section: Economic Impactssupporting
confidence: 64%
“…Waldron et al [17] who conducted an economic analysis of a leucaena-fattening system in a village in West Timor showed that under all measures of profitability, leucaena-fattening systems in representative households are profitable in the wet season, and it considerably lower in the dry season and, as would be expected, are sensitive to relative prices of feeder and finished cattle. Further, Waldron et al [17] concluded that importantly, 'returns to person days' are higher than off-farm incomes.…”
Section: Forage Developmentmentioning
confidence: 96%
“…These traditional feeding methods come with certain limitations that hinder profit maximization and productivity in cattle farming. One limitation is the lack of availability and high cost of commercial feeds [5,6,7], which can strain the financial resources of cattle farmers. Additionally, relying solely on natural pastures for grazing can lead to fluctuations in feed availability, especially during dry seasons when the quality and quantity of forage are reduced.…”
Section: Introductionmentioning
confidence: 99%